Enhanced Reinforcement Learning Model for Extraction of Objects in Complex Imaging - Usmani, U.A. (Springer Science and Business Media Deutschland GmbH, 2022)
Object segmentation is the process of extracting and partitioning an image into digital information. In the field of computer vision and image processing, we perform several activities in the segmentation stage, such as image segmentation and dynamic context video segmentation. The semantic pixel wise image segmentation method is the investigation of several objects that are extracted for image processing and interpretation. In general, segmentation relates to the partitioning of an image into full or identical regions. The effects of image segmentation have an effect on the image processing process. In general, it includes the description and specification of objects; higher order tasks follow, such as entity classification and attribute estimation. The visualization and classification of the area of interest in any picture is therefore an important function in order to segment the image. We examine a variety of image segmentation algorithms and give our reinforcement learning algorithm that uses Deep Convolutional Neural Networks for the detection of irregular objects, which has been tested on four datasets. We then relate our approaches to the previous literature to illustrate that the segmentation results are superior to the findings in the previous literature. Â© 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.